Cam Jansen and the ghostly mystery - Adler, David A.; Natti, Susanna (New York : Viking, 1996)
Cam uses her photographic memory to catch a thief disguised as a ghost.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.2
3-6
Keywords: Ghosts -- Fiction; Mystery and detective stories; Robbers and outlaws -- Fiction; Ghost stories; Mystery fiction; Thieves -- Fiction